2019
DOI: 10.3390/met10010004
|View full text |Cite
|
Sign up to set email alerts
|

The Deformation Characteristics, Fracture Behavior and Strengthening-Toughening Mechanisms of Laminated Metal Composites: A Review

Abstract: Multilayer metal composites have great application prospects in automobiles, ships, aircraft and other manufacturing industries, which reveal their superior strength, toughness, ductility, fatigue lifetime, superplasticity and formability. This paper presents the various mechanical properties, deformation characteristics and strengthening–toughening mechanisms of laminated metal matrix composites during the loading and deformation process, and that super-high mechanical properties can be obtained by adjusting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 114 publications
(163 reference statements)
0
11
0
1
Order By: Relevance
“…Generally speaking, many laminated materials exhibit excellent impact properties because of weak interfacial bonds, and delamination cracks in macroscopic fracture morphology. Previously reported that the delamination phenomenon could significantly enhance the toughness of lamination Ti‐TiBw/Ti material [35, 36]. In addition, that impact property of up to 325 J was obtained by the multi‐layer composite of medium and high carbon steel, which is much higher than that of single carbon steel [37].…”
Section: Resultsmentioning
confidence: 92%
“…Generally speaking, many laminated materials exhibit excellent impact properties because of weak interfacial bonds, and delamination cracks in macroscopic fracture morphology. Previously reported that the delamination phenomenon could significantly enhance the toughness of lamination Ti‐TiBw/Ti material [35, 36]. In addition, that impact property of up to 325 J was obtained by the multi‐layer composite of medium and high carbon steel, which is much higher than that of single carbon steel [37].…”
Section: Resultsmentioning
confidence: 92%
“…It has been reported that laminated metal composites reveal high fracture toughness due to the delamination of weak interfaces and the resultant crack‐arrester and crack‐divider effects. [ 26–28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Приведенными здесь механизмами упрочнения или разупрочнения в многослойных пленочных структурах все не исчерпывается, информация об иных возможных механизмах упрочнения приведена, например, в [20,21].…”
Section: международный симпозиум "unclassified